Illiquidity Premium in the Indian Stock Market: An Empirical Study - Kundlia, Shweta; Verma, Divya (Asian Economic and Financial Review, 2021)
India has the highest global mean illiquidity ratio (Amihud, Hameed, Kang, & Zhang, 2019), which is the primary motivation for this study. This paper aims to price the traded illiquidity and test the well-documented asset pricing models: the capital asset pricing model and the Fama & French’s (1993) three-factor model. The average annual illiquidity premium for the Indian stock market is found to be considerably high when compared to the illiquidity premiums in other developed and developing nations, suggesting that market illiquidity is of more concern to investors in India. It is also found that illiquidity augmented capital asset pricing model and illiquidity augmented Fama & French (1993) three-factor model outperforms the traditional capital asset pricing model and the Fama & French (1993) three-factor models, respectively. It is concluded that illiquidity is definitely a priced component and a key factor in designing asset pricing models for an emerging market such as India’s. Findings of the paper contribute to existing literature on liquidity and asset pricing and help investors design better investment strategies.